Prescribing pattern and pharmacoeconomic analysis of antidiabetic drugs - Goyal, Pardeep Kumar; Arora, Shalini; Mittal, Naveen; Mahajan, Bharti; Kaushal, Sandeep (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes Mellitus is a worldwide growing problem causing threat to patient’s health because of its association with various complications and comorbidities. It is a chronic disease requiring lifelong medication which further adds to the economic burden. The objective of this study was to evaluate the prescribing pattern and to do pharmacoeconomic analysis of prescribed antidiabetic drugs. Methods: This observational cross sectional study was conducted for 12 months duration in Outpatient Pharmacy of tertiary care hospital. Prescriptions with antidiabetic drugs were captured and evaluation of prescribing pattern along with pharmacoeconomic analysis of antidiabetic drugs was done. Results: A total of 611 prescriptions with antidiabetic drugs were analyzed. There were total 4034 drugs in all prescriptions with a mean of 6.6 drugs per prescription. 4.28% of drugs were prescribed by generic name and 58.9% of prescribed drugs were from essential drug list. Dual drug therapy was prescribed in maximum number of patients (42.2%) followed by monotherapy (28.8%). More commonly prescribed class of antidiabetic drugs was biguanides as monotherapy (n=119) and its combination with sulfonylureas was prescribed maximally among dual drug therapy (n=158). Cost of monthly therapy for antidiabetic drugs prescribed as monotherapy was least with Biguanides (₹ 98.89/ month) whereas combination of biguanides and thiazolidinediones was least expensive among dual drug therapy (₹ 216/ month). Conclusions: Biguanides was the most common prescribed class of antidiabetic drugs among monotherapy and its combination with sulfonylureas was most prescribed as dual drug therapy and both of these therapies were economical.